2019
DOI: 10.1186/s12954-019-0332-4
|View full text |Cite
|
Sign up to set email alerts
|

“There is a Place”: impacts of managed alcohol programs for people experiencing severe alcohol dependence and homelessness

Abstract: BackgroundThe twin problems of severe alcohol dependence and homelessness are associated with precarious living and multiple acute, social and chronic harms. While much attention has been focused on harm reduction services for illicit drug use, there has been less attention to harm reduction for this group. Managed alcohol programs (MAPs) are harm reduction interventions that aim to reduce the harms of severe alcohol use, poverty and homelessness. MAPs typically provide accommodation, health and social support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…The current focus on drug‐related deaths in Scotland may put those who consume alcohol at greater risk of harm, as their needs are relatively invisible. Our study also shows similarities to those accessing MAPs in Canada who are typically male, with high rates of daily drinking and high levels of alcohol consumption and related harm [17,18,20,36]. This suggests the need for MAPs in Scotland, given the high levels of need and current lack of appropriate services.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The current focus on drug‐related deaths in Scotland may put those who consume alcohol at greater risk of harm, as their needs are relatively invisible. Our study also shows similarities to those accessing MAPs in Canada who are typically male, with high rates of daily drinking and high levels of alcohol consumption and related harm [17,18,20,36]. This suggests the need for MAPs in Scotland, given the high levels of need and current lack of appropriate services.…”
Section: Discussionsupporting
confidence: 56%
“…Given this narrow focus within harm reduction, those who are at risk of alcohol‐related harms seem to be particularly vulnerable to being invisible within current service configurations. MAPs have been found to break the ‘vicious cycle’ of moving through multiple agencies, with people often not receiving the care they need [20]. In the current COVID‐19 pandemic, MAPs could provide safer management and supply of alcohol, in order to reduce the likelihood of withdrawal and infection of the virus [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managed alcohol programs and other alcohol-targeted interventions should be developed in homeless subjects with severe mental disorders (Pauly et al, 2019) as well as Mindfulness-Oriented Recovery Enhancement that has shown effectiveness in Co-Occurring Substance Dependence, Traumatic Stress, and Psychiatric Disorders (Garland et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is likely documentation of cultural and western treatments with First Nations peoples in that literature which has been missed. Additionally, approaches such as 'managed alcohol programs' were not within the scope of this review, but have been reported to offer some promise in improving health and wellbeing outcomes [106,107]. Community participation quality ratings may not be a true reflection on all studies' actual conduct as there may be more engagement than was recorded.…”
Section: Limitationsmentioning
confidence: 99%